Attitudes about Rehabilitation among Jail Correctional Officers - Jossie, McKenzie L. (Victims & offenders, 2023)
There are few studies that focus on jail correctional officers’ views. We surveyed officers in thirteen Florida county jails and examine the impact of personal characteristics and officer attitudes on rehabilitation attitudes, as well as differences in rehabilitative attitudes across jails. Results indicate female, nonwhite, more religious, less conservative officers, and those more satisfied with their job were more likely to support rehabilitation, while those who preferred more social distance were less likely to. Results also reveal significant differences in support for rehabilitation between jails. This study confirms that findings regarding prison officers are consistent with those for jail officers.